Evaluation of argyrophilic nucleolar organizer regions in oral tumor progression - Spolidorio, L. C.; Neves, K. A.; Soares, C. P.; Spolidorio, D. M.P.; Basso, M. F.M.; Malavazzi, I.; Almeida, O. P. (Elsevier, 2002)
The aim of this study was to compare the presence of nucleolar organizer regions (NORs) in normal oral mucosa, dysplasia and microinvasive carcinoma. All histological specimens were reviewed according to the modified classification and staging system for oral leukoplakia described by van-der-Waal et al. [Oral Oncol. 36 (2000) 264]. NOR quantification was performed with an image analyzer after staining by the argyrophilic nucleolar region technique. The morphometric results were statistically different for normal mucosa, dysplasia and microinvasive carcinoma. It was concluded that an increase of NOR activity follows the disease progression and may reflect the degree of cellular proliferation and malignancy. © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Argyrophilic nucleolar regions; Dysplasia; Oral carcinoma; Oral mucosa; Tumor progression